A proportionately increased small and equal batch delivery under consignment stock agreement for a single vendor, multiple buyers supply chain system - Kehinde Adegbola; Abdulrakib Abdulrahman (International Journal of Research in Industrial Engineering)
Consignment stocks agreement had been very useful in inventory control. The benefit ranges from improved cash flow, reduced risk level, savings on investment, reduced ownership cost, low inventory carrying cost and regular restocking to mention few. Also, small batch delivery is an effective strategy for launching a product since it enables a business to assess the market and validate the product before committing to a large production run. In this paper, we combined small batch delivery and consignment stock policy by considering a supply chain setting where a vendor fulfilled the shipment requirement of each buyer sequentially in a single production set up. To achieve this, and as against the equal size shipments policy assumed in literature for different buyers, the vendor sends a smaller shipment first as early entry, followed by n equal shipments. These n shipments are proportionately increased according to the vendor rate of production to each buyer’s demand rate. A mathematical cost function is developed to reduce the overall cost of the integrated supply chain system through the optimal cycle time and the optimal numbers of shipments to be delivered to each buyer. Numerical example is given using data from an existing literature, results were compared, and the new distribution policy gives better financial savings in terms of cost over the equal shipment policy assumed in literature. Sensitivity analyses were performed on key parameters to evaluate the robustness of the model.